2001
DOI: 10.1038/sj.leu.2402110
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte colony-stimulating factor inhibits Fas-triggered apoptosis in bone marrow cells isolated from patients with refractory anemia with ringed sideroblasts

Abstract: Treatment with granulocyte colony-stimulating factor (G-CSF) plus erythropoietin may synergistically improve hemoglobin levels and reduce bone marrow apoptosis in patients with refractory anemia with ringed sideroblasts (RARS). Fasinduced caspase activity is increased in RARS bone marrow cells. We showed that G-CSF significantly reduced Fasmediated caspase-8 and caspase-3-like activity and the degree of nuclear apoptotic changes in bone marrow from nine RARS patients. A decrease in mitochondrial membrane poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 48 publications
1
32
0
Order By: Relevance
“…Bone marrow needle aspiration and mononuclear cell isolation and cultivation were done as previously described (16,17). Mononuclear cells were cultured in medium alone or in the presence of agonistic antiFas antibodies (1 Ag/mL; clone CH-11; Medical & Biological Laboratories Ltd., Nagoya, Japan) and/or G-CSF (100 ng/mL; Neupogen, Amgen, Twelve Oaks, CA) for the indicated time points.…”
Section: Methodsmentioning
confidence: 99%
“…Bone marrow needle aspiration and mononuclear cell isolation and cultivation were done as previously described (16,17). Mononuclear cells were cultured in medium alone or in the presence of agonistic antiFas antibodies (1 Ag/mL; clone CH-11; Medical & Biological Laboratories Ltd., Nagoya, Japan) and/or G-CSF (100 ng/mL; Neupogen, Amgen, Twelve Oaks, CA) for the indicated time points.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, Fas-triggered apoptosis in bone marrow cells of MDS patients with refractory anemia with ringed sideroblasts is significantly improved by G-CSF treatment; particularly, the addition of G-CSF to CD34 þ cells improves erythroid colony formation in these patients. 164 As mentioned above, patients with more advanced stages of the MDS disease and with poor prognosis due to the presence of cytogenetic abnormalities may exhibit a condition different from that reported in MDS patients with refractory anemia (RA) or RA with ringed sideroblasts. In fact, some of these patients may exhibit an increased resistance to apoptosis instead of an increased sensitivity.…”
Section: Apoptotic Mechanisms Underlying the Defective Erythropoiesismentioning
confidence: 97%
“…[19][20][21] We have earlier shown that G-CSF decreases cytochrome c release from mitochondria to cytosol, thereby reducing caspase activation and premature death of cultured MDS erythroblasts. 22,23 However, the precise mode of the antiapoptotic action of G-CSF is still unclear.…”
Section: Introductionmentioning
confidence: 99%